Acute psychological stress increases peripheral blood CD3+CD56+ natural killer T cells in healthy men: possible implications for the development and treatment of allergic and autoimmune disorders. (July 2013) - Atanackovic, Djordje; Nowottne, Ulrike; Freier, Eva; Weber, Cora Stefanie; Meyer, Sabrina; Bartels, Katrin; Hildebrandt, York; Cao, Yanran; Kröger, Nicolaus; Brunner-Weinzierl, Monika Christine; Bokemeyer, Carsten; Deter, Hans-Christian
Abstract Acute psychological stress has primarily been investigated regarding its effects on conventional lymphocytes such as natural killer (NK) cells and CD4+ and CD8+ T cells. However, it might be important to focus on more "specialized" lymphocyte subsets, playing a role, for instance, in allergic conditions and autoimmunity, to identify links between stress, the immune system and somatic diseases. Using flow cytometry we determined frequencies of circulating T helper (Th)1-type (CD226+) and Th2-type (CRTH2+) T cells, γδ T cells, conventional CD56+ natural killer T (NKT) cells and invariant NKT cells (iNKT) in healthy young males (N = 31; median age 26 years) undergoing a laboratory computer-based stressor lasting 12 min. We found that acute psychological stress induced a prolonged increase in CD4+ and CD8+ T cells expressing a Th2 phenotype. We also detected an acute increase in CD4− and CD8− double negative γδ T cells. Finally, we found that the well-known increase in NK cells under stressful conditions was paralleled by a significant increase in numbers of conventional CD56+ NKT cells. In contrast, numbers of iNKT was not altered by stress. This study adds further evidence to a psychoneuroimmunological model proposing that under stressful conditions certain lymphocyte subsets, including iNKT and less mature T cells, are retained in lymphoid tissues while antigen-experienced effector-type T cells with a Th2 phenotype, γδ T cells and conventional CD56+ NKT cells are mobilized into the peripheral blood. We suggest that in the case of frequent stress exposure, this might result in the promotion of, for example, allergic conditions.